Does the Management Information System Causes Competitive Advantage for Banks working in Jordan? - Al Hanini, Eman Ahmad; Al Oqqaily, Samerra'a Z (International Journal of Economics and Financial Issues, 2018)
The current study aimed at identifying the role of Management Information System (MIS) in achieving competitive advantage for banks operating in Jordan. The study examined the dimensions of the following competitive advantage: cost, quality, presentation, flexibility and creativity. In order to achieve the objectives of the study, a questionnaire was distributed to the sample of 78 respondents from randomly commercial and Islamic chosen banks in Jordan. The data were analyzed through the use of the statistical analysis program SPSS. The study found that there is a statistically significant relationship between the management information systems and the achievement of a competitive advantage in banks operating in Jordan. The study recommended that banks should offer training courses for employees to raise their awareness of the importance of management information systems and their role and contribution to the excellence of the banks. The researchers also pointed out to the need of increasing bank's financial allocations to purchase machines and software that are seen to develop the business of banking. Keywords: management information systems, competitive advantage, quality. JEL Classifications: D83, G411, M41 DOI: https://doi.org/10.32479/ijefi.7135